Spontaneous Activity in Primary Visual Cortex Relates to Visual Creativity - Wang, Yibo; Li, Junchao; Wang, Zengjian; Liang, Bishan; Jiao, Bingqing; Zhang, Peng; Huang, Yingying; Yang, Hui; Yu, Rengui; Yu, Sifang; Zhang, Delong; Liu, Ming (Frontiers in Human Neuroscience, 2021)
The cognitive and neural processes underlying visual creativity have attracted substantial attention. The present research used critical time point analysis (CTPA) to examine how spontaneous activity of the primary visual area (PVA) related to visual creativity. We acquired 16 participants’ fMRI data during resting-state and performing the visual creative synthesis task. We then divided the spontaneous activity of the PVA into critical time points (CTPs) and remaining time points (RTPs) according to the CTPA. We subsequently constructed functional brain networks based on brain activity during two kinds of time points and task state brain activity separately. We explore the relationship between functional brain networks during resting-state and task fMRI. Our results found that: 1) the spontaneous activity pattern of PVA may associate with mental imagery which plays an important role in visual creativity; 2) compared with brain network based on RTPs, CTP-network showed increased global efficiency and decreased local efficiency; 3) the regional integrated properties of CTP-network could predict the integrated properties of the creative-network, while RTP-network could not. Thus, our findings indicated that the spontaneous activity of the critical time points of the primary visual area was associated with brain response evoked by the visual creative task. Our findings may provide insight how the visual cortex related to visual creativity.